All-Soft Tissue Meniscus Allograft Transplantation: Indications, Techniques, and Results - Bálint Zsidai MD; Gian Andrea Lucidi MD; Philipp W. Winkler MD; Ryan J. Gnandt MD; Ian D. Engler MD; Volker Musahl MD (SAGE Publishing, 2022)
Background: Meniscus allograft transplantation (MAT) may be indicated for young patients with joint line pain following subtotal or total meniscectomy. Several different approaches for performing MAT have been described in the literature and are influenced by appropriate patient selection, graft-sizing, and soft-tissue fixation techniques. Clinical studies demonstrate favorable results regarding pain relief and knee function in young patients undergoing MAT, making it a viable option for the treatment of postmeniscectomy syndrome. Indications: Meniscus allograft transplantation is indicated for symptomatic patients following subtotal or total meniscectomy. Selection criteria include patient age below 40 to 45 years, body mass index below 35, chondral changes of grade 2 or less, anatomic or correctable joint alignment, and normal or correctable knee stability. Technique Description: A standard arthroscopy is performed to confirm the indication for MAT, followed by debridement of the meniscus remnant up to the meniscus-capsular junction. The meniscus horns are prepared using a single No. 5 suture, while 4 to 5 No. 2 sutures are passed through the posterior body. The anterior and posterior root tunnels are drilled, and the meniscus is inserted through a posterior vertical arthrotomy using suture passers transmitted via the bone tunnels. The allograft is manipulated into proper position with a probe and the application of axial traction on the posterior root suture. At this point, sutures attached to the posterior horn are passed to the posterior capsule and 6 to 8 inside-out sutures are used to stabilize and fixate the midbody and anterior portion of the allograft. Results: Several clinical studies report good outcomes following MAT with a mean survival rate of approximately 70% at 10-year follow-up and 60% at 15 years. Additionally, some evidence is currently available regarding the long-term chondroprotective effect of MAT. Description/Conclusion: All-soft tissue meniscus allograft transplantation is a feasible approach for substitution of the damaged native meniscus and maintenance of tibiofemoral contact mechanics. Consequently, MAT is an important procedure in the toolkit of knee surgeons providing treatment for young, symptomatic postmeniscectomy patients.